FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Vino Lesmana; Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of goodcorporate governance (audit committee and institutional ownership), firm growth, and capital structure on firm value in manufacturing companies listed on IDX 2017-2019. Samples in this study using secondary data obtained from the site www.idx.co.id by using 35 companies as valid samples that have been selected using purposive sampling method. The data analysis technique was carried out by using descriptive statistics and hypothesis testing using the regression method using SPSS ver. 25 and Microsoft Excel 2019. The results of this study inicate that firm growth have no effect on firm value, while audit committee, institutional ownership, and capital structure shows that it has significant effect on firm value. The implication of this study is the need to increase institutional ownership of the company that will increase firm value in the long run